The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (De Boeck Supérieur, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."–Quatrième de couverture.
Section: xxi, 326 pages : illustrations ; 24 cm.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences